THE PEDAGOGICAL SIGNIFICANCE OF THE STEAM APPROACH IN TEACHING PROBLEMS RELATED TO PLATES - Matyakubov Jurabek Olloyorovich; Zokir Makhsudovich Ataullaev (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
In the modern education system, the process of teaching physics is becoming increasingly complex, requiring students not only to apply ready-made formulas but also to deeply analyze physical phenomena, understand their essence, and relate them to real-world processes. In particular, topics related to electric fields, including physical processes occurring between parallel plates, play a significant role in the development of students’ abstract thinking. However, practical experience shows that problems related to plates are often solved using a traditional approach based solely on formulas, which hinders students’ deep understanding of the subject.